The reason why the companion Ibn Abbas changed his opinion on riba al-fadl - Tahir, Ibrahim Nuhu (International Association of Computer Science and Information Technology Press (IACSIT), 2016)
This paper aims to explain an important element that should be avoided in business dealings for them to be permissible. The interest to conduct this research was sparked by a fatwah given by some contemporary scholars. The fatwah says that Riba al-Fadhl does not exist in currency exchange, which inspired the selection of this topic. The objective of this research is to disclose the truth of the matter. In addition it aims to awaken the awareness of people of concern and to draw their attention to what really happened during the early days of the companions regarding the said issue. The reader is enlightened with clear evidence that shows that the above fatwa is wrong. The Prophet (sallallahu alaihi wasallam) said: "Gold for gold, silver for silver, wheat for wheat, barley for barley, dates for dates, and salt for salt - like for like, equal for equal, and hand-to-hand; if the commodities differ, then you may sell as you wish, provided that the exchange is hand-to-hand"